2022
DOI: 10.1007/s40258-022-00772-7
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L Population Norms for Italy

Abstract: Objectives This study aimed to provide normative data obtained in response to the EQ-5D-5L questionnaire in Italy and compare this with data from other countries. Methods A sample of the Italian adult population (aged ≥ 18 years) was recruited and interviewed online using videoconferencing software (Zoom) between November 2020 and February 2021. The distribution of answers was estimated as per the descriptive system of the EQ-5D-5L, and descriptive statistics were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
5
2
Order By: Relevance
“…This study found that HRQoL increased with age category. The opposite trend has been reported in many settings, with HRQoL (utility scores) generally decreasing as age increases, such as in Vietnam [ 24 ], Italy [ 19 ], Portugal [ 33 ], South Australia [ 25 ] and Poland [ 21 ]. As the data were weighted to the Australian population, this is unlikely to be due to a sample error.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study found that HRQoL increased with age category. The opposite trend has been reported in many settings, with HRQoL (utility scores) generally decreasing as age increases, such as in Vietnam [ 24 ], Italy [ 19 ], Portugal [ 33 ], South Australia [ 25 ] and Poland [ 21 ]. As the data were weighted to the Australian population, this is unlikely to be due to a sample error.…”
Section: Discussionmentioning
confidence: 95%
“…This method requires non-negative values, therefore the disutility value (disutility = 1-utility value) was entered as the dependent variable [ 24 ]. Based on recently reported EQ-5D-5L population norms, it was hypothesised that older people and females were expected to have higher disutility scores and were entered first in the GLM (Model 1) [ 19 , 33 , 34 ]. Analyses were conducted using R studio and IBM SPSS Statistics 28.0 [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardized Italian version of the EuroQoL (EQ‐5D‐5L) (Meregaglia, Malandrini, Finch, Ciani, & Jommi, 2023) was used to assess the quality of life in young cancer survivors. It is made up of five questions assessing five dimensions (mobility, self‐care, usual activity, pain/discomfort and anxiety/depression) and one item on a visual analogue scale for self‐rating scale.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of the larger Italian EQ-5D-5L valuation study [ 11 , 12 ] approved by the Ethics Committee of Bocconi University in October 2020 (approval number: 2020-SA000136.4). In the Italian valuation study, 1183 interviews were collected between October 2020 and February 2021 by 11 interviewers via videoconferencing administration, following the EQ-VT protocol [ 13 ].…”
Section: Methodsmentioning
confidence: 99%